2020
DOI: 10.1371/journal.pone.0240084
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic use of chest CT for screening osteoporosis and predicting the risk of incidental fracture in breast cancer patients: A retrospective longitudinal study

Abstract: This study aimed to investigate the diagnostic performance of chest computed tomography (CT) for opportunistic screening and longitudinal follow-up of osteoporosis in breast cancer patients, compared to dual-energy X-ray absorptiometry (DXA). The association between L1 vertebral attenuation on chest CT and incidental fracture was also evaluated. We retrospectively reviewed 414 consecutive breast cancer patients who underwent both non-enhanced chest CT and DXA within a 3-month interval and had at least two DXA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
(33 reference statements)
0
21
0
1
Order By: Relevance
“…All these results and the tendency are similar to the lumbar spine or low-dose chest CT measured by PB-QCT ( Ghildiyal et al, 2018 ; Cheng et al, 2021 ). The reliability and accuracy of HU to BMD measurement and determining osteoporosis have been proven in the literature with many reports ( Lee et al, 2013 ; Park et al, 2020 ), but in its current state, it is not ready for clinical implementation. There is a lack of exchangeability among different machines that limits its broad applicability ( Gausden et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…All these results and the tendency are similar to the lumbar spine or low-dose chest CT measured by PB-QCT ( Ghildiyal et al, 2018 ; Cheng et al, 2021 ). The reliability and accuracy of HU to BMD measurement and determining osteoporosis have been proven in the literature with many reports ( Lee et al, 2013 ; Park et al, 2020 ), but in its current state, it is not ready for clinical implementation. There is a lack of exchangeability among different machines that limits its broad applicability ( Gausden et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…If the L1 vertebra was non-homogeneous, not visualized, or fractured, the measurement was performed from the next intact vertebra (thoracic 12th vertebra) ( 21 ). Based on previous studies, a vertebral BMD value of 100 HU was accepted as lower density ( 13 , 22 ).
Figure 2 Computed tomography (CT) images showing region of interest (ROI) placement in the first lumbar vertebra (L1) of a patient.
…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that frailty caused by decreased function and strength of the musculoskeletal system due to aging affects the prognosis of various diseases ( 11 ). Recent feasibility studies suggest that vertebral attenuation can be used to assess the loss of bone mineral density (BMD) in the screening of osteoporosis characterized by low bone mass and quality, increasing bone fragility and fracture risk ( 12 , 13 ). A low BMD value has been reported to be a critical prognostic factor in many benign and malignant diseases such as coronary artery disease, chronic obstructive pulmonary disease (COPD), cerebrovascular conditions, and breast cancer ( 13 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opportunistic screening using chest computed tomography, in 414 consecutive breast cancer patients, who underwent both DXA and computed tomography, was recently tested. A moderate correlation between L1 attenuation and DXA T-score was observed, and women with attenuation values 90 HU or lower had higher fracture risk [30]. Screening using vertebral fracture assessment (VFA) to identify vertebral fractures in SUPERB-cohort of 3028 women in Sweden, was able to identify additional women at high fracture risk.…”
Section: New Studies On Reducing the Treatment Gapmentioning
confidence: 96%